The role of public support for the film industry – an analysis of movie production incentives in Europe - Orankiewicz, Agnieszka (Rola wsparcia publicznego w przemyśle filmowym – analiza zachęt dla produkcji filmowej w Europie, 2022)
The European model of financing culture implies state intervention. In fact, in every European country, film production is supported directly or indirectly by the state, creating a complex system of financing film production. The choice of audiovisual support systems affects the development of national culture and film industries as well as the sector’s resilience to crises, especially in the long term. The study focused on the development of an incentive system for supporting the audiovisual sector in European countries. The aim of the paper was to identify the mechanisms and motivations for supporting the domestic production of films and to analyse the public support for local audiovisual industries. The author reviewed the literature and conducted a comparative analysis of incentive systems supporting the audiovisual sector in European countries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 2, s. 90-104
Keywords: film production; public support; fiscal incentives; management in culture; produkcja filmowa; wsparcie publiczne; zachęty podatkowe; zarządzanie w kulturze